Managerial accounting : creating value in a dynamic business environment - Hilton, Ronald Walter , 1949- (McGraw-Hill/Irwin, 2011)
Emphasises on teaching students to use accounting information to best manage an organization. This title covers contemporary topics such as activity-based costing, target costing, the value chain, customer profitability analysis, and throughput costing, including traditional topics such as job-order costing, budgeting and performance evaluation